(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Metabolic Syndrome is a complex metabolic condition which is a rising therapeutic problem in modern society. Additionally, it has been linked to the emergence of CVD, Type 2 DM and other grave health issues. It primarily develops as a result of a diet high in fat, a sedentary lifestyle, stress, insomnia, drinking too much alcohol, being overweight, and other factors. When three out of the five biochemical and physiological abnormalities such as visceral obesity, dyslipidemia, hypertension, increased blood sugar, insulin resistance, etc. are present in the body, it is considered clinically diagnosed. Acharya Charaka has mentioned a group of diseases namely Santarpana Nimittaj Vikara (diseases caused due to over eating) which can be symptomatically co-related with metabolic syndrome, especially Medaavrit (covered by fatty tissues) Vata (one of the three bodily humors representing air in the body). Aims & Objectives: Comparative evaluation of Virechana Karma (therapeutic purgation) and Lekhana Basti (a type of therapeutic enema) in the management of metabolic syndrome. Material & Methods: 43 patients were selected on the basis of classical symptomatology of metabolic syndrome from OPD and IPD of Dept. of Panchakarma, Hospital of Rishikul Campus and randomly divided into two groups - Virechana group and Lekhana Basti group on the basis of inclusion - exclusion criteria. There after the patients were subjected for detailed clinical history and physical examination. Statistical analysis used: Since objective criteria were selected so for intragroup comparison Paired- t- test was applied and for intergroup comparison Unpaired- t- test (t-test) was applied. Conclusion: Virechana Karma is better than Lekhana Basti in the management of metabolic syndrome.